Comments in relation to the resolution of the Supreme Court of 19 Octo-ber 2018, III CZP 45/18 (Ius Novum, 2019)
The analysis of the resolution was to determine which property will cover an asset acquired by a matrimony as a result of a legal transaction in exchange for funds in part coming from matrimonial property and in part for funds coming from one of the spouses’ personal property (spouses’ personal properties) that are subject to the principle of substitution. Sharing the arguments of the Supreme Court, in dogmatic terms, the first standpoint approved by the representatives of the legal doctrine seems most appropriate: it provides that if an asset is acquired with funds contributed from two funds, the asset is assigned to personal property or joint property as a result of a comparison of the volume of funds coming from both properties – the major part of the spending would be the decisive criterion.
Keywords: joint matrimonial property; principle of substitution; allocation of assets; financial settlement; joint property; separate properties